2020
DOI: 10.3390/ijms21020495
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characterization of Packaging Foils Coated by Chitosan and Polyphenols Colloidal Formulations

Abstract: In this research, antimicrobial polysaccharide chitosan was used as a surface coating for packaging material. The aim of our research was to establish an additive formulation of chitosan and antioxidative plant extracts as dispersion of nanoparticles. Chitosan nanoparticles with embedded thyme, rosemary and cinnamon extracts were synthesized, and characterized for this purpose. Two representative, commercially used foils, polypropylene (PP) and polyethylene (PE), previously activated by UV/ozone to improve coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 42 publications
10
59
0
Order By: Relevance
“…Furthermore, chitosan itself shows very poor antioxidant behavior and, thus, it has no significant effect on the phenolic content. The highest total phenolic content was observed for chitosan nanoparticles with embedded cinnamon extract (CSNPs CIN), which correlates with the result for pure cinnamon, as the richest in phenolic substances [23]. Table 2 reports oxygen transmission rates for untreated reference PE and PP foil and functionalized foils, which is an extremely important property to control food spoilage.…”
Section: Minimal Inhibitory Concentration (Mic)supporting
confidence: 61%
See 4 more Smart Citations
“…Furthermore, chitosan itself shows very poor antioxidant behavior and, thus, it has no significant effect on the phenolic content. The highest total phenolic content was observed for chitosan nanoparticles with embedded cinnamon extract (CSNPs CIN), which correlates with the result for pure cinnamon, as the richest in phenolic substances [23]. Table 2 reports oxygen transmission rates for untreated reference PE and PP foil and functionalized foils, which is an extremely important property to control food spoilage.…”
Section: Minimal Inhibitory Concentration (Mic)supporting
confidence: 61%
“…The final amount of the extract, which was encapsulated into chitosan nanoparticles and further applied onto the foil surface, was 4× its MIC, in order to obtain good antimicrobial activity of functionalized foils. The total phenolic contents of thyme, rosemary, and cinnamon, as well as of chitosan nanoparticles with embedded extracts, were already reported and discussed in our previous paper [23]. It was shown that the concentration of phenols in extract solutions was the highest in cinnamon, followed by rosemary and then thyme.…”
Section: Minimal Inhibitory Concentration (Mic)mentioning
confidence: 56%
See 3 more Smart Citations